Managing Uncertainty: Immigration Policies in Spain during Economic Recession (2008-2011) - Ana LÓPEZ-SALA (El Colegio de la Frontera Norte, A.C., 2013)
The global economic crisis has changed the landscape of immigration dynam ics and migration policies management in Spain, introducing a new immigration order. In this new context, the instruments used to manage migration have been reinvented and readapted to meet the objectives of an immigration policy that has radically changed. The aim of this article is to analyze how the current crisis has af fected labor migration flows to Spain and how they are managed and governed. The focus is on changes in policies between 2008 and 2011. There has been a shift from a policy whose principal objective was to recruit workers to meet the demands of the labor market to a policy that focuses on improving the employ ability of unemployed resident immigrants, the promotion of pay-to-go programs and the maintenance of social and economic integration policies.